Evaluation of the adsorption capacity of surfactant-modified biomass in an aqueous acid blue 193 system - A. Hashem; Chukwunonso O. Aniagor; S. Farag; M. Fikry; A.A. Aly; A. Amr (Waste Management Bulletin, 2024)
The study explored the capacity of modified pinewood dust (S-dust) for adsorbing acid blue 193 dye. The novel adsorbent was prepared via the insitu intercalation of quaternized ammonium copolymer (cationic surfactant) onto pinewood dust. The synthesized biosorbent was characterized using the Fourier Transform Infrared (FTIR), Scanning Electron Microscopy (SEM), Energy Dispersion X-ray (EDX) and Brunauer–Emmett–Teller (BET) surface area equipment. To establish the variable effects on the dye uptake, the ranges of solution pH, initial adsorbate concentration, contact time and adsorbent dosage were varied. The maximum monolayer adsorption capacity of 117.58 mg/g was recorded at pH 4.0, 0.1 g/L adsorbent dose and 2 h sorption duration. The process kinetics and isotherm modelling fitted best to the pseudo-first-order and Freundlich models, respectively. From the mechanistic/diffusion studies, intraparticle and pore diffusion mechanisms were respectively postulated at low and high initial adsorbate concentrations. Also, the occurrence of a nonspontaneous endothermic uptake process was inferred from the thermodynamics evaluations. Therefore, the effective acid blue 193 dye uptake onto novel S-dust was confirmed in this study.